A case study of short-term exposure to hybrid learning. (1st June 2020) - Kim, Min Kyu; Margulieux, Lauren
In this study, we: 1) investigated whether short-term use of online/off-campus learning modules would help instructors and students engage in teaching and learning if class schedules were abruptly switched to online; 2) suggested design improvements for short-term hybrid intervention. We assumed that the supportive features of hybrid learning would benefit students with low motivation and negative feelings prior to short-term online intervention. We used a mixed-methods approach, gathering data from two typical on-campus undergraduate classes. The results show that student emotions significantly differed before and after the short-term online intervention. These findings aligned with comments made by the students. The instructors reported positive effects of the online pedagogy due to the affordances of network technologies. Participant reflections suggested four design improvements: clear goals, cohesive alignment, clear guidance and feedback, and technologies with which students are familiar.